DEVELOPMENT OF HEYZINE-BASED E-COMIC MEDIA TO IMPROVE LEARNING OUTCOMES IN PANCASILA EDUCATION FOR FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Hidayah, Nurul; Widodo, Susilo Tri (STKIP Citra Bakti, 2026)
The lack of utilisation of technology-based learning media at Karanganyar 01 State Primary School is one of the factors affecting student learning outcomes. This study aims to develop and test the feasibility, practicality, and effectiveness of Heyzine-based E-Comic media. It uses a Research and Development (R&D) approach based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The population in this study involved 28 fourth-grade students at Karanganyar 01 Public Elementary School. The data collection techniques used were tests (pre-test and post-test) and non-tests in the form of observations, questionnaires, interview results, and documentation. Feasibility was assessed through expert validation, which showed that the Heyzine-based E- Comic media was